Consistency check of photon beam physical data after recommissioning process - B. Kadman (2018)
© Published under licence by IOP Publishing Ltd. In radiotherapy, medical linear accelerator (Linac) is the key system used for radiation treatments delivery. Although, recommissioning was recommended after major modification of the machine by AAPM TG53, but it might not be practical in radiotherapy center with heavy workloads. The main purpose of this study was to compare photon beam physical data between initial commissioning and recommissioning of 6 MV Elekta Precise linac. The parameters for comparing were the percentage depth dose (PDD) and beam profiles. The clinical commissioning test cases followed IAEA-TECDOC-1583 were planned on REF 91230 IMRT Dose Verification Phantom by Philips' Pinnacle treatment planning system. The Delta4PTwas used for dose distribution verification with 90% passing criteria of the gamma index (3%/3mm). Our results revealed that the PDDs and beam profiles agreed within a tolerance limit recommended by TRS430. Most of the point doses and dose distribution verification passed the acceptance criteria. This study showed the consistency of photon beam physical data after recommissioning process. There was a good agreement between initial commissioning and recommissioning within a tolerance limit, demonstrated that the full recommissioning process might not be required. However, in the complex treatment planning geometry, the initial data should be applied with great caution.